Madrasah Principal Management in the Development of Human Resources of Senior High Schools in Jambi - Abdullah; Samsu; Badarussyamsi (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
This study aims to analyze the management of madrasah principals in developing human resources in Madrasah Aliyah in Jambi Province. Effective human resource development is very important to improve the quality of education and madrasah operations. This study uses a qualitative approach with field research methods, through in-depth interviews, observations, and documentation of several madrasah principals in various Madrasah Aliyah in Jambi Province. The results of the study indicate that the strategies implemented by madrasah principals include teacher professional development through ongoing training, regular performance assessments, and the creation of a collaborative and innovative work environment. Madrasah principals also pay attention to the welfare of teachers and staff by providing adequate support, both financially and non-financially. Challenges faced include budget constraints and lack of access to external professional training. In conclusion, good madrasah principal management plays an important role in developing quality HR, which has a direct impact on improving the quality of education in Madrasah Aliyah in Jambi.